Ergonomics development needs in truck body design – from video analyses to solution proposals. (1st January 2012) - Reiman, Arto; Putkonen, Ari
Truck drivers need improvements on their work environment in ergonomics and safety issues. In this study, participative video analyses were performed to identify areas of discomfort and the risks drivers face when working outside the cab. Analyses resulted in identification of 262 discomfort and risk factors of which roughly half occurred in trucks and trailers. Due to the findings, a web questionnaire was used to investigate what kind of participative product design aspects truck body and trailer manufacturing companies apply currently. Accordingly, the need for participation is recognised but these companies lack such systematic procedures and methods. This study also introduces a procedure to utilise the identified risks and discomforts for developing the design and development requirements. The procedure has led to new solutions that are currently utilised in different interest groups' processes. The procedure supports participation by all stakeholders and may be used in product design processes in environments where a mutual understanding is crucial for eliminating the recognised safety problems in practice.